piRNA-mediated transgenerational inheritance of an acquired trait - Grentzinger, Thomas; Armenise, Claudia; Brun, Christine; Mugat, Bruno; Serrano, Vincent; Pelisson, Alain; Chambeyron, Séverine

(untitled) (Genome Research, 2012)
The maintenance of genome integrity is an essential trait to the successful transmission of genetic information. In animal germ cells, piRNAs guide PIWI proteins to silence transposable elements (TEs) in order to maintain genome integrity. In insects, most TE silencing in the germline is achieved by secondary piRNAs that are produced by a feed-forward loop (the ping-pong cycle), which requires the piRNA-directed cleavage of two types of RNAs: mRNAs of functional euchromatic TEs and heterochromatic transcripts that contain defective TE sequences. The first cleavage that initiates such an amplification loop remains poorly understood. Taking advantage of the existence of strains that are devoid of functional copies of the LINE-like I-element, we report here that in such Drosophila ovaries, the initiation of a ping-pong cycle is exclusively achieved by secondary I-element piRNAs that are produced in the ovary and deposited in the embryonic germline. This unusual secondary piRNA biogenesis, detected in the absence of functional I-element copies, results from the processing of sense and antisense transcripts of several different defective I-element. Once acquired, for instance after ancestor aging, this capacity to produce heterochromatic-only secondary piRNAs is partially transmitted through generations via maternal piRNAs. Furthermore, such piRNAs acting as ping-pong initiators in a chromatin-independent manner confer to the progeny a high capacity to repress the I-element mobility. Our study explains, at the molecular level, the basis for epigenetic memory of maternal immunity that protects females from hybrid dysgenesis caused by transposition of paternally inherited functional I-element.